MANAJEMEN KEUANGAN KELUARGA PADA ANGGOTA PKK PURI RHABAYU RT 008/RW 015 BATAM - Hermaya Ompusunggu; Anggun Permata Husda; Triana Ananda Rustam (JUPADAI : Jurnal Pengabdian Kepada Masyarakat, 2022)
The COVID-19 pandemic has indirectly forced every household in the family to look for alternatives from various solutions related to financial management because it has an impact on the household economy. Household financial management is a science that must be possessed by every woman or mother in their household. Learning to manage or manage the economy in the family is very important in the household. No matter how big the income is, poor management will disrupt the financial stability of the family. Apart from that, in order to improve the family economy, it is also necessary to think about finding new business opportunities that can be relied on to increase the family's financial resources. Talking about financial stability, the main and crucial problem in the family is around finances. There are many possibilities that can happen, it could be due to lack of money, excess money or because you don't find the right way to manage a mediocre income while needs will always exceed receipts or income. Therefore this community service aims to provide knowledge to mothers within the scope of the PKK located at Puri Rhabayu RT 008/RW015 Batam City. This service targets community development in the hope that housewives can manage their finances.